2014
DOI: 10.1111/sms.12212
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament injury after more than 20 years: I. Physical activity level and knee function

Abstract: Little is known about physical activity level and knee function including jump capacity and fear of movement/reinjury more than 20 years after injury of the anterior cruciate ligament (ACL). Seventy persons with unilateral ACL injury participated (23 ± 2 years post-injury): 33 treated with physiotherapy in combination with surgical reconstruction (ACLR ), and 37 treated with physiotherapy alone (ACLPT ). These were compared with 33 age- and gender-matched controls. Assessment included knee-specific and general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(128 citation statements)
references
References 40 publications
2
120
2
Order By: Relevance
“…Proprioceptive and strength deficits (Kramer et al, 1993;Tengman et al, 2014;Timmins et al, 2016a) seem to be reasonable hypotheses, but the current results suggest that poor eccentric strength is an unlikely explanation for high hamstring injury rates in athletes with prior ACLR. Opar and colleagues (2015a) and Timmins and colleagues (2016b) have shown that weakness in the Nordic hamstring exercise was associated with an elevated risk of HSI in elite Australian Rules Football and Soccer cohorts, respectively.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Proprioceptive and strength deficits (Kramer et al, 1993;Tengman et al, 2014;Timmins et al, 2016a) seem to be reasonable hypotheses, but the current results suggest that poor eccentric strength is an unlikely explanation for high hamstring injury rates in athletes with prior ACLR. Opar and colleagues (2015a) and Timmins and colleagues (2016b) have shown that weakness in the Nordic hamstring exercise was associated with an elevated risk of HSI in elite Australian Rules Football and Soccer cohorts, respectively.…”
Section: Discussionmentioning
confidence: 64%
“…A number of observational studies (Konrath et al, 2016;Nomura et al, 2015;Takeda et al, 2006) have reported decrements in concentric (Tengman et al, 2014) and eccentric (Tengman et al, 2014;Thomas et al, 2013) knee flexor strength in the years following surgery as well as reduced muscle size (Nomura et al, 2015) and altered muscle architecture of the ST (Timmins et al, 2015). However, these studies are almost always constrained by small sample sizes, and several investigations have found conflicting results regarding the recovery of strength after rehabilitation (Aglietti et al, 1994;Ejerhed et al, 2003).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations